The Prophet Muhammad is An Example of Laying the Principles of Peace: In Light of the Facts of the Prophet’s Biography - سليماني، عبدالقادر أحمد (جامعة الأميرة نورة بنت عبد الرحمن, 2020)
And after, there is no doubt that the Prophet (peace and blessings of Allah be upon him) has followed the trace of the prophets and messengers before him, and he took their guidance by the command of the Almighty Allah in his saying, ﴾They are those whom Allah had guided.so follow their guidance) (Al-An’aam: 90) There is no doubt that his command, (peace and blessings of Allah be upon him), is a matter for all of us, because he's our role model, and his nation followed him in what he legitimizes and orders them to do, also because Almighty Allah says): ﴾Indeed in the messenger of Allah (Muhammad peace and blessings of Allah be upon him) you have a good example to follow﴿. [Al-Ahzab: 21], so his biography (peace be upon him), A track record of exploits, how not !! It is a comprehensive biography that surrounds all life phases, conditions and affairs, and it is a historical fact, validated by true history and cannot be denied. This research comes to show the reality of the example of the Prophet, peace and blessings be upon him, in establishing the principle of peaceful coexistence in light of the facts of the Prophet’s biography. The example of the Prophet in laying the foundations of a culture of peace and security with different religious denominations. And the importance of role models for the Prophet (peace and blessings of Allah be upon him) in establishing principles of peaceful coexistence in the communication of contemporary societies.
لا شك أن النبي صلى الله عليه وسلم قد اتبع أثر الأنبياء والرسل قبله، وأخذ بهديهم، وذلك بأمر الله عز وجل في قوله: (أُولئِكَ الَّذِينَ هَدَى اللَّهُ فَبِهُداهُمُ اقْتَدِهْ) (الأنعام: 90) ولا شك أن أمره صلى الله عليه وسلم أمر لنا جميعا، لأنه قدوتنا، وأمته تبع له فيما يشرعه ويأمرهم به، ولأن الله تعالى يقول: (لَقَدْ كَانَ لَكُمْ فِي رَسُولِ اللَّهِ أُسْوَةٌ حَسَنَةٌ) (الأحزاب: 21)، لذلك كانت سيرته صلى الله عليه وسلم، سجل حافل بالمآثر، كيف لا!! وهي سيرة جامعة محيطة بجميع أطوار الحياة وأحوالها وشؤونها، وهي حقيقة تاريخية، يصدقها التاريخ الصحيح ولا يتنكر لها. ويأتي هذا البحث ليبين حقيقة قدوة النبي صلى الله عليه وسلم في إرساء مبدأ التعايش السلمي في ضوء وقائع السيرة النبوية. وقدوته صلى الله عليه وسلم في إرساء أسس ثقافة السلم والأمن مع مختلف الطوائف الدينية. وأهمية قدوة النبي صلى الله عليه وسلم في إرساء مبادئ التعايش السلمي في تواصل المجتمعات المعاصرة.
Keywords: السيرة النبوية -- القدوة -- محمد صلى الله عليه وسلم -- التعايش السلمي -- مستخلصات الأبحاث